The Religion of the Israelites as Described in the Bible - CHEN, Yiyi (Journal of Research for Christianity in China (JRCC), 2025)
Today, Christianity and Judaism are two biggest religions in the world. They have something in common and something not. Most Christians believe that Jesus is the Son of God, fully divine and fully human, and the savior of humanity prophesied in the Old Testa- ment. Consequentially, Christians refer to Jesus as Christ or Messiah. Judaism is considered by religious Jews to be the expression of the covenantal relationship God established with the Children of Israel. In this article, it presents the differences from religions in the bible and modern religions. Also, it will show us characterizes of God and the relationship between God and Israelites at that time based on the Bible and archaeological data.